International Reserves and Central Bank Independence - Samano, Agustin (World Bank, Washington, DC, 2021)
This paper proposes a novel theory of reserve accumulation that emphasizes the role of an independent central bank. Motivated by a positive correlation between reserve accumulation and central bank independence in Latin America, the paper develops a quantitative sovereign default model with an independent central bank that can accumulate a risk-free foreign asset. The findings show that if the central bank is more patient than the government and as patient as households are, in equilibrium, the government issues more debt than what is socially optimal, and the central bank accumulates reserves to undo government over-borrowing. A key insight is that the government can issue more debt for any level of reserves but chooses not to because doing so would increase sovereign spreads, making it more costly to borrow. Quantitatively, the analysis finds that the central bank independence channel accounts for 75 percent of the average reserve levels observed in Mexico from 1994 to 2017. Finally, the paper shows that accumulating reserves improves social welfare. Welfare gains come from reducing the costs of front-loading public spending.